Manajemen Konflik dalam Memperbaiki Penilaian Evaluasi Pembelajaran Siswa - Ananda, Hairani Alfi; Julaiha, Siti; Sudadi, Sudadi; Bahrani, Bahrani; Ramli, Akhmad (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The research aims to learn, solve, and repair the student learning evaluation assessment in Madrasah Ibtidaiyah Negeri 1 Samarinda through conflict management. The research only focuses on the headmaster, representative of headmaster for curriculum, and teacher. This research used qualitative research by using descriptive approach. Data collection technique used observation and interview. Data analysed by using conflict management theory and other supporting theories. The results show the headmaster and the representative of headmaster said the whole of learning activities in the school run well. But, the conflict occurred from the teacher. The teacher said only a few teachers know how to give students learning evaluation assessment by using methods, not only predicting the score of each student directly and randomly that can be called as shoot or pulley the score without having the steps of learning evaluation. The conclusion, there is a lack of the role of headmaster and representative of headmaster for curriculum to observe and give the guidance to the teacher to do evident and clear learning evaluation for students’ assessment.